PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN DIGITAL MARKETING TERHADAP KEPUASAN PELANGGAN AUNTIE ANNE’S AEON MALL JAKARTA GARDEN CITY - Aryo Utomo Nugroho (LPPM Universitas Asa Indonesia, 2021)
The purpose of this research is to determine the effect of product quality, price perception and digital marketing on customer satisfaction at the Auntie Anne’s AEON Mall Jakarta Garden City. The population in this study are the customers of Auntie Anne’s AEON Mall Jakarta Garden City. The sample used in this study was 100 people by purposive sampling method. The data collection by accidental technique using the designed questionaire. The Questionaire has been tested of its validity and reliability prior to distribution. Data were analyzed by descriptive and quantitative. The regression analysis started with the classical assumption test (normality, multicolinearity, heteroscedasticity and linearity test) afterward by multiple linear regression analysis. The model determined by the hypotheses testing applied F test, t test and correlation test and the coefficient of determination (R2). The results showed that product quality has a significant influence on customer satisfaction, price perception has a significant effect on customer satisfaction, digital marketing has a significant effect on customer satisfaction, where all variables have a positive effect on customer satisfaction simultaneously at the Auntie Anne’s AEON Mall Jakarta Garden City